(3RHOI GdEUhds - (3eMeO Hf MSjf GdMGQKj GdgeOGfj GdYGedj, HgGA GdOjf , J (B1031 (3g` s
(3ChdgG (B:s
(3hHYO ajbhd QGLi YahQHg GdZfi eMeO GdeTJgQ HgGA GdOjf s
(3BNQgG (B:s
(3eKfi hKdGK hQHGY s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B102s
Keywords: (3CUhd Gdabgs